2019
DOI: 10.1080/16549716.2019.1662682
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of community resilience in addressing the Ebola virus disease epidemic in Liberia: a qualitative study (community resilience in Liberia)

Abstract: Background: There is an increasing recognition that community resilience plays a significant role in addressing health shocks like the Ebola virus disease (EVD) epidemic. However, the factors that constitute community resilience, and how these operate dynamically with other health system factors are less understood. Objective: This paper seeks to understand key factors that constitute community resilience and their role in responding to the EVD outbreak in Liberia. Methods: Key informant interviews were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 37 publications
1
107
0
3
Order By: Relevance
“…General practitioners and other health professionals are also important stakeholders as the public often trust information received from health professionals over that received through public health campaigns ( 6 ) or other community sources ( 51 ). The government, particularly those government officials involved in disseminating public health advice, are also vital stakeholders given the way in which trust might be built or eroded depending on the conduct of these communicators ( 52 ). Governments and public health officials produce pandemic response plans which guide government action and communication to the public.…”
Section: Applying a Model For Developing And Maintaining Public Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…General practitioners and other health professionals are also important stakeholders as the public often trust information received from health professionals over that received through public health campaigns ( 6 ) or other community sources ( 51 ). The government, particularly those government officials involved in disseminating public health advice, are also vital stakeholders given the way in which trust might be built or eroded depending on the conduct of these communicators ( 52 ). Governments and public health officials produce pandemic response plans which guide government action and communication to the public.…”
Section: Applying a Model For Developing And Maintaining Public Trustmentioning
confidence: 99%
“…During pandemics, responsibility for management falls to government working in consort with public health officials and the health professions. Within the pandemic-trust literature, this has contributed to a focus on trust in government ( 42 , 50 , 51 ), healthcare industry ( 42 ), public health organizations ( 6 , 42 , 54 , 55 ), communicators of public health messages ( 22 , 52 , 56 ), and the communicated messages themselves ( 57 ). Effective pandemic management has been associated with “agreed communication strategies, [a] clear division of responsibilities” and agreed policy guidelines (35, p. 21).…”
Section: Issues To Consider In Applying the Trust Modelmentioning
confidence: 99%
“…They may also indirectly boost psychological well-being by offering a buffer against the adverse consequences of individual or contextual stress (Diez Roux and Mair 2010; Liu et al 2017). Previous studies have revealed that neighborhoods with more developed social infrastructure are more resilient to disasters, such as earthquakes, hurricanes, extreme weather, and the Ebola epidemic, because they preserve a higher level of cooperation, trust, and mutual support (Alirol et al 2011;Alonge et al 2019;Klinenberg 2018;Norris et al 2008). Scholars have also observed that strong neighborhood governance, civic participation, trust in institutions, willingness to follow the government's advice and instructions, can influence how COVID-19 epidemic unfolds in a neighborhood (Djalante, Shaw, and DeWit 2020;Hynes et al 2020;Wu 2020).…”
Section: Neighborhood Social Infrastructure Social Cohesion and Menmentioning
confidence: 99%
“…A study in Hubei province revealed that trust in government increased public acceptance of and compliance with control measures during COVID-19 pandemic (Wu 2020). Maintaining a positive outlook can, in turn, promote residents' mental health (Alonge et al 2019).…”
Section: Neighborhood Social Infrastructure Social Cohesion and Menmentioning
confidence: 99%
“…The surveillance system is a priority during the outbreak 10 Sepers, et al, 34 (2018) Participatory study Needs a comprehensive monitoring and evaluation system 11 Alonge, et al, 18 (2019) Interviews with stakeholders Leadership, social bonding, trusted information, social trust affected community resilience during the outbreak 12 Rabelo, et al, 28 (2016) Focus group discussions Feeling worried, lack of respect, motivation, hope, isolated 13 Siu, et al, 30 (2016) Phenomenology Sociocultural factors using personal protective equipment 14 Respati, et al, 14 16,17 To achieve a holistic-comprehensive goal of community planning, thus discussions among the local government and stakeholders are needed in the first weeks of the pandemic. 18 A holistic-comprehensive surveillance system helps health professionals and policymakers to better understand the pandemic disease and develop public health policy for preventing the spread of infectious disease and promoting health behaviors. Information on the COVID-19 collected should include sufficient information on the current state of pandemic disease and the epidemiology of the infectious disease.…”
Section: Best Practices To Implement a Holistic-comprehensive Approachmentioning
confidence: 99%